Preliminary study on simultaneous adsorption of nitrate and phosphate using CaFe2O4-modified biochar originated from lychee peels - Lan Huong Nguyen; Tuan Hiep Tran (Vietnam Journal of Science, Technology and Engineering, 2024)
In this study, lychee peels derived-biochar modified with CaFe2O4NPs (MLPB) were successfully fabricated to adsorb simultaneously both nitrate (NO3-) and phosphate (PO43-) from aqueous solution. The preliminary investigation on the effect of operational parameters, including pyrolysis temperature and modification ratio on adsorption of nitrate (NO3-) and phosphate (PO43-) in single-component and bi-component systems was performed. The characteristics of biochar (PLPB) and magnetic modified biochar (MLPB) were evaluated through the specific surface area, SEM, EDS and mapping, FTIR, and XRD. The primary results showed the adsorption of NO3- and PO43- onto PLPB reached a peak at the pyrolysis temperature of 450oC with a NO3- and PO43- adsorption capacity of 12.8 and 10.9 mg/g, respectively, in the single-component system while the adsorption capacity of NO3- and PO43- in the bi-component system was 12.5 and 10.6 mg/g, respectively. The removal efficiency of NO3- and PO43- maximised at a modification ratio of 5%. At this modification ratio, the adsorption capacity of NO3- and PO43- in the single-component reached, respectively, 24.0 and 21.5 mg/g while the adsorption of NO3- and PO43- was 24.0 and 22.6 mg/g in the bi-component system, respectively. The preliminary study on analysing characteristics of the adsorbent confirmed that the removal of NO3- and PO43- was through ligand exchange and surface complexation mechanisms. The findings indicated that the MLPB was a feasible and fully promising adsorbent in the simultaneous removal of NO3- and PO43- from the aqueous solution.